LANDSLIDE VULNERABILITY MAPPING USING FUZZY LOGIC METHOD FOR DISASTER MITIGATION: Case Study of Bungaya District, Gowa Regency - Amirin Kusmiran; Jusniati; Ayusari Wahyuni; Minarti Minarti; Muhammad Tajuddin (Department of Physics, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2025)
Landslides are a significant threat to the Bungaya District in Gowa Regency, Indonesia, with five incidents recorded in 2019. This study aimed to map landslide vulnerability using the Fuzzy Logic method implemented in ArcGIS software and propose appropriate mitigation strategies. The analysis incorporated six parameters: rainfall intensity, soil type, elevation, slope, land cover type, and geology. The results revealed four categories of vulnerability: not vulnerable (592.91 ha), low (3,093.32 ha), medium (9,139.72 ha), and high (7,557.29 ha). Areas with high vulnerability were characterized by steep topography, easily eroded soil and rock types, and inappropriate land-use practices. Rannaloe, Sapaya, Bissoloro, and Buakkang villages were classified as highly susceptible to landslides. Mitigation strategies were proposed based on the vulnerability level, with a combination of technical and vegetative methods recommended for high- and moderate-vulnerability areas, whereas vegetative methods alone were deemed sufficient for low-vulnerability regions. This study contributes to advancing spatially informed disaster risk management by integrating susceptibility mapping with actionable mitigation recommendations tailored to the vulnerability levels identified in the Bungaya District.